Detection of Seed Borne Fungi of Sunflower (Journal of Plant Disease Sciences, 2023)
Because of adaptation to varied weather conditionsandsoil types, sunflower is the fourth most significant oilseed crop grown worldwide. Fungi play an important role in influencing grain and seed storage quality. The current study was conducted to investigate seed-borne fungi associated with sunflower seeds. Sunflower cultivar seed samples namely TAS-82, PKV SF-9, EC-68414, Morden, Surya, DRSF-108, SS-56, and LSF-8 were collected and analysed for seedmyco-flora using standard blotter and agar plate procedures. Alternaria alternata, Aspergillus flavus, Aspergillus niger, Cladosporium spp., Curvularia lunata, Fusarium oxysporum, Fusarium semitectum, Penicillium spp., Rhizoctonia bataticola, and Rhizopus species were identified as seed- borne myco-flora in two detection methods. The standard blotter approach outperformed over the agar plate method for detecting seed myco-flora because the number of colonies of seed myco-flora was greater in the standard blotter method. Morden had the highest association of seed borne myco-flora among all types, followed by TAS-82, and LFS-8 had the lowest association of seed borne myco-flora by both detection methods.
Keywords: Sunflower; Detection; Seed myco-flora; Varieties